2023
DOI: 10.1038/s41413-023-00246-z
|View full text |Cite
|
Sign up to set email alerts
|

Managing the immune microenvironment of osteosarcoma: the outlook for osteosarcoma treatment

Abstract: Osteosarcoma, with poor survival after metastasis, is considered the most common primary bone cancer in adolescents. Notwithstanding the efforts of researchers, its five-year survival rate has only shown limited improvement, suggesting that existing therapeutic strategies are insufficient to meet clinical needs. Notably, immunotherapy has shown certain advantages over traditional tumor treatments in inhibiting metastasis. Therefore, managing the immune microenvironment in osteosarcoma can provide novel and val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 505 publications
0
48
0
Order By: Relevance
“…The survival status of osteosarcoma patients was still poor due to drug resistance, recurrence, or metastasis (Wang et al, 2023). It's reported that the 5-year survival rates in osteosarcoma remained at 60%−70% in recent 20 years (Tian et al, 2023). Until now, the target therapy and immunotherapy in osteosarcoma still lack response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survival status of osteosarcoma patients was still poor due to drug resistance, recurrence, or metastasis (Wang et al, 2023). It's reported that the 5-year survival rates in osteosarcoma remained at 60%−70% in recent 20 years (Tian et al, 2023). Until now, the target therapy and immunotherapy in osteosarcoma still lack response.…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma is the most malignant primary bone tumor, which mainly happens in adolescents (Tian et al, 2022; Tian et al, 2023). At present, the treatment of osteosarcoma patients is still mainly chemotherapy combined with surgery (Chang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…[9] However, due to the unique physiological environment of OS mentioned above, the efficiency of nano drug delivery systems in OS treatment remains limited. [10] Drug delivery in OS is a cascade process at both tissue and cellular level. Although bone-targeting drug delivery systems can improve the drug enrichment in tumor sites, [11] the drug internalization in cancer cells is still limited due to the dense stromal tissue of OS.…”
Section: Introductionmentioning
confidence: 99%
“…Hence there is a clinically unmet need for biomarkers that can stratify patients into meaningful subgroups and open avenues for precision oncology. With the absence of a clear druggable, driving molecular target in Osteosarcoma 2 , several groups have turned their attention towards the tumor microenvironment (TME) aiming to identify immune-related transcriptional signatures associated with favorable prognosis [3][4][5][6][7][8][9][10][11] . However, due to shortage of data, the prognostic value of most signatures has not been comprehensively evaluated in multiple external cohorts, especially in the context of clinically established prognostic features such as the stage of disease at diagnosis and percent tumor necrosis following neoadjuvant chemotherapy 12 .…”
Section: Introductionmentioning
confidence: 99%